Tag-Aware Personalized Recommendation Using a Hybrid Deep Model - Xu, Z; Lukasiewicz, T; Chen, C; Miao, Y; Meng, X (AAAI Press/International Joint Conferences on Artificial Intelligence, 2017)
Recently, many efforts have been put into tag-aware personalized recommendation. However, due to uncontrolled vocabularies, social tags are usually redundant, sparse, and ambiguous. In this paper, we propose a deep neural network approach to solve this problem by mapping the tag-based user and item profiles to an abstract deep feature space, where the deep-semantic similarities between users and their target items (resp., irrelevant items) are maximized (resp., minimized). To ensure the scalability in practice, we further propose to improve this model’s training efficiency by using hybrid deep learning and negative sampling. Experimental results show that our approach can significantly outperform the state-of-the-art baselines in tag-aware personalized recommendation (3.8 times better than the best baseline), and that using hybrid deep learning and negative sampling can dramatically enhance the model’s training efficiency (hundreds of times quicker), while maintaining similar (and sometimes even better) training quality and recommendation performance.